Exchange students' unique experiences during Covid-19 : To stay or leave? - Sirva, Ella (My University, 2021)
The purpose of this study is to examine the experiences of exchange students in Finland during Covid-19 pandemic. The pandemic started at the beginning of 2020, which caused universities among other things to be closed down. Future exchange periods were mainly moved or cancelled. International mobility was almost totally stopped for a while. The focus in this study is specifically on the impact of immobility and mobility in constructing an exchange experience. The main research question is “How the (im)mobility during a pandemic affected the students exchange experiences?” followed by two sub questions, which are interested in the student’s own actions, resources and agency in constructing an exchange experience. This study consists of eight semi-structured interviews, that were conducted in the summer of 2020. The interviewees were exchange students who were studying in Finland when the pandemic started. The data has been analyzed with qualitative content analysis in a concept driven way. The main concepts in this study are agency, especially international student agency, and Bourdieu’s different forms of capitals. This study is a part of a bigger research project called “Equality, (Im)mobility structures and International students: A study of international students’ experiences during the pandemic in Finland”. From the findings of this study it is clear to see that mobility is one of the most important factors in creating an exchange experience. The students either left or stayed in Finland when the pandemic started. The students had different push and pull factors that affected their decision. Especially the effect of social, economic and cultural capital could be found from the student’s stories. The ones who ended their mobility period did not really have an exchange experience. Those who stayed had a really unique exchange experience and they stayed mobile in different ways inside of Finland. The student’s own agency and the will to make the experience the best it could be really had an impact on their time abroad. For those who stayed the pandemic did not ruin their exchange experience, it just changed it. The findings suggest that there should be better support systems for exchange students. The universities and Erasmus network could all learn and develop from this crisis if something similar will happen in the future.
Keywords: Covid-19, Exchange students, International students, Agency, Capital, Bourdieu, Erasmus